(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
The integration of digital technologies into English as a Foreign Language (EFL) classrooms has reshaped instructional methodologies in Uzbekistan. While these innovations enhance interactivity and accessibility, they also introduce a growing pedagogical challenge known as digital distraction. This phenomenon refers to the reduction of sustained learner attention due to simultaneous exposure to multiple digital stimuli such as multimedia content, online platforms, and mobile devices. This study examines the impact of digital distraction on attention regulation and English language acquisition in Uzbek EFL contexts. Using a qualitative-analytical approach supported by cognitive learning theories, the research explores how attention shifts affect comprehension, vocabulary retention, and communicative competence. Findings suggest that although technology increases engagement, uncontrolled digital exposure significantly disrupts cognitive processing. The study emphasizes the need for structured digital pedagogy to balance engagement and attention control in language learning environments.